Isolated Short Femur Length in the Third Trimester - Shakya, Ipsa; Neupane, Bishomber; Agrawal, Ritul; Bajgain, Arun; Darshan, Chaitanya (Journal of Nobel Medical College, 2023)
A short femur length (FL) has been defined as the presence of a biometric value of fetal FL below the 5th percentile or −2 standard deviations (SD) for gestational age at ultrasound examination. A short FL was also defined as a biparietal diameter to FL ratio above 1.5 SD for gestational age or as observed to expected FL ratio ≤0.91 for gestational age. Short FL was considered isolated when both the estimated fetal weight and abdominal circumference were >10th percentile for GA. Here, we report a case of a pregnant patient with isolated short FL of fetus in third trimester ultrasound exam.